Microbial functional diversity covaries with permafrost thaw‐induced environmental heterogeneity in tundra soil - Mengting M. Yuan; Jin Zhang; Kai Xue; Liyou Wu; Ye Deng; Jie Deng; Lauren Hale; Xishu Zhou; Zhili He; Yunfeng Yang; Joy D. Van Nostrand; Edward A. G. Schuur; et al. (Global Change Biology, 2018)
Permafrost soil in high latitude tundra is one of the largest terrestrial carbon (C) stocks and is highly sensitive to climate warming. Understanding microbial responses to warming‐induced environmental changes is critical to evaluating their influences on soil biogeochemical cycles. In this study, a functional gene array (i.e., geochip 4.2) was used to analyze the functional capacities of soil microbial communities collected from a naturally degrading permafrost region in Central Alaska. Varied thaw history was reported to be the main driver of soil and plant differences across a gradient of minimally, moderately, and extensively thawed sites. Compared with the minimally thawed site, the number of detected functional gene probes across the 15–65 cm depth profile at the moderately and extensively thawed sites decreased by 25% and 5%, while the community functional gene β‐diversity increased by 34% and 45%, respectively, revealing decreased functional gene richness but increased community heterogeneity along the thaw progression. Particularly, the moderately thawed site contained microbial communities with the highest abundances of many genes involved in prokaryotic C degradation, ammonification, and nitrification processes, but lower abundances of fungal C decomposition and anaerobic‐related genes. Significant correlations were observed between functional gene abundance and vascular plant primary productivity, suggesting that plant growth and species composition could be co‐evolving traits together with microbial community composition. Altogether, this study reveals the complex responses of microbial functional potentials to thaw‐related soil and plant changes and provides information on potential microbially mediated biogeochemical cycles in tundra ecosystems.